Teacher’s Job Satisfaction and Organizational Commitment in High Schools Within Maela Refugee Camp, Thailand - Thawda, Naw Marvel (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
The sustainable development goals recently published by the UN state that all children should have access to education. However, diverse populations, including teachers at refugee schools, are facing challenges in providing quality education for the students due to the lack of support and motivation. In order to improve teachers' work performance, it is important to consider what teachers need to increase their job satisfaction and organizational commitment. The purpose of this study was to discover teachers’ levels of job satisfaction and organizational commitment in High Schools within the Maela refugee camp, Thailand. This study was designed using a correlational and descriptive survey design. The study sample was 156 respondents selected using a convenience sampling procedure. The questionnaires were given to teachers who were willing to participate in this study. Data were analyzed quantitatively. The result showed that the overall level of teachers’ job satisfaction and organizational commitment was neutral despite the fact that teachers were not really satisfied with the pay they received. The highest qualification attained was the factor that had the most impact on job satisfaction when comparisons were made between teachers’ age, years of experience, and position. A weak significant relationship was found between teachers’ job satisfaction and organizational commitment (n = 156, r =0.35). This research can be used to inform the future policies and procedures aimed at enhancing teachers' job satisfaction. Keywords : Teacher, job satisfaction, organizational commitment, refuge camp